Editorial - Duarte Almada, Emmanuel; Cerqueira do Nascimento Borba, Rodrigo (Revista Interdisciplinar Sulear, 2021)
Educação do Campo, Educação Ambiental e Movimentos Sociais: interseções e atravessamentos em debate